2015
DOI: 10.12973/iji.2015.8214a
|View full text |Cite
|
Sign up to set email alerts
|

Computer Assisted Project-Based Instruction: The effects on Science Achievement, Computer Achievement and Portfolio Assessment

Abstract: The purpose of this study is to compare the effects of computer assisted projectbased instruction on learners' achievement in a science and technology course, in a computer course and in portfolio development. With this aim in mind, a quasiexperimental design was used and a sample of 70 seventh grade secondary school students from Org. Eşref Bitlis Primary School in Istanbul was selected. The students were randomly assigned to one of the two groups: the control group and experimental group. Instruction to cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 11 publications
0
18
1
2
Order By: Relevance
“…The implementation of project-based learning collaborated with Information, and Communication Technologies (ICT) can generate a positive learning environment where the students can actively participate in the process of knowledge and skills construction [8]. The higher learning advantage will be obtained if the instruction given is assisted with computer technology compared to traditional methods [9].…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of project-based learning collaborated with Information, and Communication Technologies (ICT) can generate a positive learning environment where the students can actively participate in the process of knowledge and skills construction [8]. The higher learning advantage will be obtained if the instruction given is assisted with computer technology compared to traditional methods [9].…”
Section: Introductionmentioning
confidence: 99%
“…At the end of the study, the findings revealed that science and technology, as well as portfolio assessment scores from the experimental group, were significantly higher than the control group. These results indicate that the benefits of learning are higher when instruction is provided by computeraided project-based instruction than by traditional methods [24].…”
Section: Relevant Research On the Use Of E-learning Mediamentioning
confidence: 84%
“…Project-based collaboration arouses student learning motivation. The inclusion of cellular technology with designs that lead to learning activities can be done anywhere, actively, and collaboratively (Erdogan, Y, & Dede, D, 2015).…”
Section: Motivate D 37%mentioning
confidence: 99%